Measurement of the W-boson helicity in top-quark decays from $t\bar{t}$ production in lepton+jets events in pp collisions at $\sqrt{s} =$ 7 TeV - CMS collaboration (2220 authors) (2013)
The W-boson helicity fractions in top-quark decays are measured with ttbar events in the lepton+jets final state, using proton-proton collisions at a centre-of-mass energy of 7 TeV, collected in 2011 with the CMS detector at the LHC. The data sample corresponds to an integrated luminosity of 5.0 inverse femtobarns. The measured fractions of longitudinal, left-, and right-handed helicity are F0 = 0.682 +/- 0.030 (stat.) +/- 0.033 (syst.), FL = 0.310 +/- 0.022 (stat.) +/- 0.022 (syst.), and FR = 0.008 +/- 0.012 (stat.) +/- 0.014 (syst.), consistent with the standard model predictions. The measured fractions are used to probe the existence of anomalous Wtb couplings. Exclusion limits on the real components of the anomalous couplings gL, gR are also derived.